2001
DOI: 10.1054/bjoc.2000.1714
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of mitochondrial depolarization from cytochrome c release during apoptosis induced by photodynamic therapy

Abstract: Photodynamic therapy (PDT) with the phthalocyanine photosensitizer Pc 4 induces rapid apoptosis in mouse lymphoma (LY-R) cells, initiating with the release of cytochrome c from mitochondria. It has been proposed that the opening of the mitochondrial membrane permeability transition pores, which results in the dissipation of the mitochondrial membrane potential (Δψ m ), is essential for the escape of cytochrome c from mitochondria into the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 45 publications
11
76
1
Order By: Relevance
“…Amounts of cytosolic cytochrome c were essentially equal, despite the higher MMP loss in WTK-1 versus TK6 cells. These findings are consistent with previous reports that cytochrome c release was independent of MMP loss after treatment of cells with diverse agents (39,40). In addition, many investigations have revealed that the antiapoptotic proteins Bcl-2 and Bcl-x͞l block p53-regulated release of cytochrome c from mitochondria (6,10,38).…”
Section: Discussionsupporting
confidence: 92%
“…Amounts of cytosolic cytochrome c were essentially equal, despite the higher MMP loss in WTK-1 versus TK6 cells. These findings are consistent with previous reports that cytochrome c release was independent of MMP loss after treatment of cells with diverse agents (39,40). In addition, many investigations have revealed that the antiapoptotic proteins Bcl-2 and Bcl-x͞l block p53-regulated release of cytochrome c from mitochondria (6,10,38).…”
Section: Discussionsupporting
confidence: 92%
“…Following a PBS wash, cells were suspended in culture medium containing the fluorescent probe JC-1 (10 g/ml) for 10 min and then analyzed by flow cytometry. 42 …”
Section: Detection Of Mitochondrial Depolarization In Cultured Cellsmentioning
confidence: 99%
“…Most types of cancers are especially active in both the uptake and accumulation of photosensitizer agents than normal tissues, which makes tumors especially vulnerable to PDT (8). PDT employs a photosensitizer and visible light to produce singlet oxygen and other reactive oxygen species, which cause an oxidative stress in cells and membrane damage which eventually leads to cell death and tumor ablation (9)(10)(11). PDT was reported to inhibit cancer through different cell death pathways and its effectiveness is dependent on the types of cancer cell lines and photosensitizers (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%